CONSTRAINTS FACED BY PERSONS WITH DISABILITIES IN EMPLOYMENT - Dhanda, Poonam; Kumar Mishra, Alok (International Journal of Research -GRANTHAALAYAH, 2016)
The study is absolutely an observational study used to measure empowerment of persons with disabilities through the improvement of entrepreneurial quality, development and imagination. Further research is expected to create, assess, evaluate, the significance of present study in other developing nations. India is frequently depicted as a developing yet a youthful nation. As the nation enters its 65th year of autonomous presence the depiction of youth does not appear to be excessively suitable. It can now be termed youthful by reason of the way that half of its billion or more populace comprises of persons underneath 25 years old and 65% of the populace is beneath 35 years. Every single differently abled individual has a leftover potential force than their non-disabled companions. Six to seven rate of populace in India is individuals with inability almost 8 to 9 crore individuals the number is expanding with mishaps and maturing. About 33% of aggregate number of individuals in India is influenced with some kind of incapacity.